2002
DOI: 10.1086/340218
|View full text |Cite
|
Sign up to set email alerts
|

Outbreaks of Adult Gastroenteritis Traced to a Single Genotype of Rotavirus

Abstract: Between November 1998 and December 2000, the Centers for Disease Control and Prevention screened samples from 263 outbreaks of gastroenteritis in the United States and identified 3 that were associated with rotavirus among adults. Rotaviruses from each outbreak were further characterized by reverse-transcription polymerase chain reaction. Surprisingly, all specimens were of serotype G2, a strain that is, as determined by high-stringency hybridization analysis, genetically distinct in all 11 gene segments from … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
33
1
1

Year Published

2004
2004
2006
2006

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 58 publications
(35 citation statements)
references
References 13 publications
0
33
1
1
Order By: Relevance
“…This observation may be in contrast to data from many previous reports in which rotavirus gastroenteritis outbreaks affecting older children and adults were attributed to infection with G2P [4] strains (18,27). When G1P [8] rotaviruses found in different age groups were further analyzed by electropherotypes, it appeared that the detection of one codominant strain, E9, deviated toward the younger age group, whereas the detection of the other codominant strain, E3, deviated toward the older age group (Table 3).…”
Section: Discussioncontrasting
confidence: 86%
“…This observation may be in contrast to data from many previous reports in which rotavirus gastroenteritis outbreaks affecting older children and adults were attributed to infection with G2P [4] strains (18,27). When G1P [8] rotaviruses found in different age groups were further analyzed by electropherotypes, it appeared that the detection of one codominant strain, E9, deviated toward the younger age group, whereas the detection of the other codominant strain, E3, deviated toward the older age group (Table 3).…”
Section: Discussioncontrasting
confidence: 86%
“…This pathogen infects not only children but also adults (12,16), and rotavirus infection may occur repeatedly in humans from birth to old age (17). Young children are the most vulnerable subjects, and the prevalence of infection differs by age.…”
Section: Rotavirus Infectionmentioning
confidence: 99%
“…It is thought that homotypic immune response to rotavirus correlated with protection against severe diarrhea, and heterotypic antibodies within a genogroup may also be important for protection from secondary infections [Bishop et al, 1983;Offit, 1996;Velazquez et al, 1996]. Primary infections with G1 type followed by symptomatic infection with G2 type have been described by Linhares et al [1988] and symptomatic G2 infections in adults have also been reported [Timenetsky et al, 1996;Griffin et al, 2002]. In a study in South Africa, it was demonstrated that a temporal distribution with peaks in the prevalence of G2 strains after 10 years could be observed [Page and Steele, 2004a].…”
Section: Introductionmentioning
confidence: 99%